Federal innovation platform: reproductive health of 1st year students of Smolensk State Medical University - Ekaterina A. Minchenkova; Tatyana A. Gustovarova; Larisa S. Kirakosyan; Anna V. Krikova; Elena V. Dmitrieva (ZAO "Consilium Medicum", 2022)
Aim. To study the state of reproductive health of female students of Smolensk State Medical University according to the 2020 monitoring data. To analyze the real picture of sexual life and reproductive health of first-year female students. To consider the necessity of including additional medical examinations in the dispensary monitoring plan. Materials and methods. We examined 507 first-year female students aged 1827 years at Smolensk State Medical University. The examination included the collection of complaints, general and obstetric-gynecological history, questionnaires, gynecological examination, general clinical examination, pelvic ultrasound, microscopic and oncocytological smears, pH-metry of vaginal secretions, colposcopy. Statistical data processing included methods of descriptive statistics. Construction of the 95% confidence interval was done according to the formula for fractions and frequencies by the Wald method. Significance of the difference between the studied features was assessed using Fisher's angle transformation. Statistical significance was considered at 95% (p0.05) and 99% (p0.01) probability. Statistical analysis of the results was performed in Microsoft Excel 2016 using the AtteStat 12.0.5. Results. The examination of female students of Smolensk State Medical University revealed reproductive health disorders and lack of awareness of modern contraceptives. The study concluded that an ultrasound examination of the ovarian tract, colposcopy, endocrinologist consultation, examination of hormonal background, and STI examination should be added to the plan of dispensary observation. Conclusion. The data obtained in the course of the present study indicate that modern first-year female students have an insufficient level of reproductive education that does not meet the requirements of our time. In our opinion, the scientific and practical project will help to increase competence and responsibility in health saving issues to improve and strengthen reproductive health, to develop and implement a set of measures in the form of clinical and diagnostic research of the reproductive system, informational and educational lectures on the prevention of abortion, infertility and other diseases, sexual education, and in the future to affect the demographic situation.